THE EFFECT OF TIME DIFFERENCES AND HAULING DURATION TOWARDS BOAT LIFT NETS FISHING CATCH IN DEMAK WATERS (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Demak had two fish auction which is still active, namely Morodemak and Wedung. Based on survey results in Morodemak Coast Fishing Port Demak, there are boat lift nets totaled 69 units. Fishers use boat lift nets of fishing gear in Morodemak waters to catch anchovy (Stolephorus sp.). This study aimed to analyze the composition of fishing results, analyze the effect of time differences on the fishing results, and analyze the effect of Hauling duration towards boat lift nets catches. The method used in this study is descriptive, and the data collection method consists of observation, interviews, literature study, and documentation. In this research, there were ten times of Boat Lift Nets fishing trip. The results are that the total weight of catches at 18.30–22.30 was 4,487.82 Kg less than the total weight of catches at 24.00–04.00, which was 6,563.18 Kg. The total weight of catches on 20–27.5 minutes Hauling is 6,601.9 Kg greater than The total weight of catches on 27.6–35 minutes Hauling is 4,449.1 Kg. Based on the results, there are significant effects between fishing catch duration on the Hauling process towards boat lift nets catches, which can be operated continually at Demak waters.